Conflict and Improvisation by Design: the metaphor of Repente - Kirschbaum, Charles; Sakamoto, Cristina Yumi; de Vasconcelos, Flávio Carvalho (Organizações & Sociedade, 2014)
The Jazz metaphor was introduced in Organizational Studies aiming to encourage the adoption of practices that could lead to a greater degree of improvisation. This appropriation was made assuming a high degree of cooperation, as opposed to highly formalized organizations where routines are taken as rigid routines, source of inertia. This article appropriates from this literature, seeking first to extend the idea of organizational routines, emphasizing the interpretationist dimension, pointing out the role of conflict and finally reviewing the heuristic value of the dichotomy between “collapse of sensemaking” and “sensemaking”. This reappropriation allows us to prepare the ground for the introduction and analysis of the Repente metaphor and subsequently to compare it with the metaphor of Jazz. We attempt to show how the structures of Repente allow improvisation while protecting each opponent’s space. This setting is important when one takes conflict as the predominant vector for improvisation.